LARGE FIRES AND FIRE DANGER INDICES IN ‘GOVERNADOR’ INDIGENOUS TERRITORY, MARANHÃO STATE - Miranda, Guido José Donagemma; Mendonça, Bruno Araujo Furtado de; Oliveira, Emanuel Renato Sousa de; Oliveira, Kamilla Andrade de; Romeiro, Joyce Machado Nunes; Torres, Fillipe Tamiozzo Pereira (Floresta, 2022)
Large fires are global environmental problems, increasingly recurrent due to climate change, with severe perspectives for the future. The present study characterized the edaphoclimatic conditions of the Governador Indigenous Territory (TI), Amarante do Maranhão - MA, as well as analyzed the influence of these conditions on large burn scars (over 50 ha) and fire danger indices in the period from 2001 to 2018. The scars were mapped on TM and OLI Landsat images and the following fire danger indices were assessed: Telicyn Logarithmic Index; Nesterov Index; Monte Alegre Formula (FMA) and Modified Monte Alegre Formula (FMA +); and the Canadian Fire Weather Index (FWI). The results indicate that the Governador TI region is a critical area in terms of wildfires, with large impacted areas and climatic conditions with great fire risks. In addition, savanna formations, which predominate in the region, are highly prone to fires, as well as pastures in the surroundings. The Monte Alegre Formula index stands out with the best result, as well as the great correlation with climate and vegetation data, highlighting the period from June to August and savanna formations as the most critical conditions.